2003
DOI: 10.1046/j.1467-2494.2003.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

pH‐induced alterations in stratum corneum properties

Abstract: Skin-cleansing compositions based on alkyl carboxylates (soaps) have a higher irritation potential than those based on syndet surfactants such as alkyl isethionates or alkyl ether sulphates. Contributing factors include inherent differences in the irritation potential of soaps and syndet surfactants, pH-induced changes in surfactant solution chemistry, and the direct effects of pH on the physical properties of the stratum corneum (SC). Past work has not directly addressed the effect of solution pH on the SC it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 21 publications
(20 reference statements)
0
35
1
Order By: Relevance
“…Soap-based cleansers are known to have a higher potential to irritate skin than syndets (77-82). Ananthapadmanabhan and colleagues (83) have demonstrated that high-pH solutions even in the absence of surfactants increase SC swelling and lipid rigidity. The higher pH of soap bars may be a contributing factor in the higher irritation potential of soap bars compared to syndet bars.…”
Section: Cleansersmentioning
confidence: 99%
“…Soap-based cleansers are known to have a higher potential to irritate skin than syndets (77-82). Ananthapadmanabhan and colleagues (83) have demonstrated that high-pH solutions even in the absence of surfactants increase SC swelling and lipid rigidity. The higher pH of soap bars may be a contributing factor in the higher irritation potential of soap bars compared to syndet bars.…”
Section: Cleansersmentioning
confidence: 99%
“…70% (i.e., about 2.5 g water/g dry tissue) at 100% RH or when immersed in water [37,39]. A pronounced swelling is associated with water immersion [40] and a considerable reduction in the YoungÕs modulus. Tensile experiments show that values for this parameter decrease from %1 GPa at 50% RH [41] to a value of %3 MPa in water [42].…”
Section: Friction Of Skin In the Wet Statementioning
confidence: 99%
“…However, a decrease in the number of infants with higher TEWL indicated that this combination skin care could improve lower cutaneous barrier function. It is important to maintain the infant skin surface at a weakly acidic pH to allow the development of skin barrier function,15 but some reports have indicated that skin pH is transiently raised by cleansing with soap, liquid surfactants, or water 13. The skin surface pH on the face, buttocks, and the flexor of the arm was decreased in both the lotion group and in the cream group.…”
Section: Discussionmentioning
confidence: 99%
“…It is hard to produce a fine foam without the use of a sponge or towel, but the use of these can naturally harm fragile infant skin because of excessive rubbing. The benefits of a weakly acidic base for cleansers have been also reported 12,13. We have therefore designed a mild acidic cleanser with less surfactant, which could be used as a fine-textured foam through a dispenser.…”
Section: Introductionmentioning
confidence: 91%